Live foods for juveniles production of blue swimming crab, Portunus pelagicus (Linnaeus, 1766) - Mhd, Ikhwanuddin; Azra, M.N.; yik sung, Yeong; A.B., Abol-Munafi; Shabdin, Mohd Long (Academic Journals Inc., 2012)
The study were aim to demonstrate the affects of live food type’s i.e., mixed diatom, Artemia nauplii and rotifer on survival rate and molt time of larvae stage till 1st day juvenile crabs (C1) of P. pelagicus. Three types of feeding regimes given to the crab larvae through out the study trials are with and without mixed diatom, with and without Artemia nauplii and with and without rotifer. The study shows that zoea fed with rotifer alone was not enough to sustain survival in the next zoea stages and to promote metamorphosis up to megalopa stage. Survival of zoea fed with Artemia nauplii alone shows that this type of food is not suitable for the very early zoea stages. The study also shows that the adding of mixed diatom to larvae rearing system where rotifer and Artemia nauplii is main food items did not produced high survival rate as compared to larvae rearing fed on rotifer and Artemia nauplii alone. The results of the study demonstrated that the food types not only effect survival rate but also the growth of crab larvae. The study generally ended that the combination diet of rotifer and Artemia nauplii alone is enough to produced C1